Numerical Simulation of Chemical Non-equilibrium Flow for Ablative Flow Fields in Near Space - Han, Zheng; Li, Haiyan; Li, Zhihui; Luo, Wanqing; Li, Ming; Zhang, Jiazhong (Journal of Environmental Accounting and Management, 2026)
A numerical method has been established and applied to compute the chemical non-equilibrium flow involving ablative chemical reaction and flow interference effect in near space, where the chemical non-equilibrium Navier-Stokes equation is solved by taking account of 23 species including the ablative products. The computational results of electron number density in plasma sheath for sphere-cone RAMC(Radio Attenuation Measurement C plan)-II are well compared with those of flight experiments. The reliability of the present method has been validated, and the varying feature of the electron number density with flight altitude has been revealed. The present numerical method is applied to compute the Teflon ablative flow field and flow interference in near space past sphere-cone body with different altitudes. It is indicated that the effect of ablative products on electron number density is mainly limited in the region of boundary layer while the phenomena of Teflon ablation are obvious at moderate and low altitudes. The decrease of temperature in the boundary layer is caused by the Teflon ablation which results in the increase of the number of negative ions. On the other hand, the number of chemical species F- increases continuously with the decrease of flight altitude resulted from the reaction between electron and electrophilic species of Teflon-air reactive mixtures. These factors cause the reduction of electron number density in the boundary layer, specially flow interference and characteristics around the wreckages generated by multiple disintegration of the Tiangong-type vehicle in expiration of service during off-orbit reentry.